Management Of Active Deep Learner Experience Training In Improving Learning Quality - Hartini, Dewi; Suherman, Usep (AIM: Journal of Islamic Education Management, 2024)
Education is a basic need in the era of globalisation that plays an important role in improving the quality of life and progress of the nation. Countries that have quality education will produce superior human resources and contribute to national development. Therefore, improving the quality of learning through teacher training is very important. This research uses a qualitative approach with a field research design. Data were collected through observation and in-depth interviews with teachers and students at SMPN 3 Baleendah and SMP Mathla'ul Anwar Margahayu. ADLX learning planning at Mathla'ul Anwar Margahayu Junior High School includes integration of Islamic values, improving teacher competence, and using information technology. ADLX implementation at SMPN 3 Baleendah and SMP Mathla'ul Anwar Margahayu improved students' engagement and motivation, as well as their learning outcomes. Teachers reported improved skills in classroom management and use of interactive learning media. Evaluation results showed an increase in students' average test scores. ADLX combining Active Learning, Deep Learning and Experiential Learning proved effective in improving the quality of learning. Changes in classroom management create an interactive and dynamic learning environment. Technology support and innovation in learning methods enrich students' learning experience. The implementation of ADLX at SMPN 3 Baleendah and SMP Mathla'ul Anwar Margahayu has improved the quality of education. Innovative learning strategies and the use of technology create an effective and interactive learning environment. This success can be an example for other schools.